Successful combination of endoscopic and laparoscopic removal of multiple ingested needles: A case report - Tsuruya, Kota (Medicine (Baltimore), 2020)
RATIONALE: Foreign body (FB) ingestion is a relatively common clinical situation in the emergency department. However, multiple sharply pointed foreign bodies located in different organs are rare conditions and no definite treatment guidelines has been established. PATIENT CONCERNS: A 31-year-old amateur magician visited the outpatient clinic with a chief complaint of epigastric discomfort. He might have accidentally swallowed some needles while practicing a magic trick 2 days before. DIAGNOSIS: Imaging tests revealed 1 needle was stuck in the left liver lobe through the stomach wall, 1 was in the third portion of the duodenum, 3 were in the ascending colon, and 2 were in the transverse colon. INTERVENTIONS: A needle in the duodenum and 5 in the colon were removed by endoscopy. The needle stuck in the liver from the stomach was not visible inside the stomach and was successfully removed by laparoscopy a few days later. OUTCOMES: The patient was able to tolerate an oral diet and was discharged on postoperative day 4 without any complications. LESSONS: Developing a treatment plan in cases of multiple sharp FB may be difficult. A multidisciplinary team of endoscopists and surgeons is needed to determine the best possible treatment plan. This experience illustrates the importance of the planning of the sequence and method of removal of multiple foreign bodies from the gastrointestinal tract.